A Study of Personal Financial Planning Among Young Adults - Mazlifah , Mubarak Ali (2011)
The purpose of this study is to gauge the level of understanding on financial education and the importance of financial planning among young adults. For the purpose of this study five items under financial planning were being examined which are saving management,credit management, insurance planning,investment planning and retirement planning. Data were collected through questionnaires distributed among young adults. Results showed that the majority level of understanding on financial education is low.The highest knowledge level is only average. Further result showed that,majority of the young adults cannot differentiate the importance of financial planning under the 4 categories of financial planning except for retirement planning.This is proven via answers given in the retirement planning category.Last but not least,the results also showed that demographic profile such as gender,age, marital status, number of dependents, education level, working sector and monthly income is the secondary influence in determining the level of importance in financial planning.